Sublingual immunotherapy in children: facts and needs - Frati Franco; La Rosa Mario; Incorvaia Cristoforo; Marseglia Gian; Marcucci Francesco (BMC, 2009)
Abstract Allergen specific immunotherapy (SIT) is the practice of administering gradually increasing doses of the specific causative allergen to reduce the clinical reactivity of allergic subjects, and is the only treatment targeting the causes of hypersensitivity and not only the symptoms, as done by drugs. The traditional, subcutaneous immunotherapy (SCIT) was burdened by the problem of systemic reactions which may be sometimes severe and - though very rarely - even fatal. This was the background to develop non injections routes for SIT and particularly sublingual immunotherapy (SLIT), that emerged as a real treatment option for respiratory allergy. A number of studies was conducted to evaluate efficacy and safety of SLIT, the first meta-analysis - including 22 placebo-controlled trials - concluded for positive results in both issues, but the number of studies on children was too low to draw definite conclusions. Since then, many other studies became available and make possible to analyze SLIT in children in its well defined aspects as well as in sides still requiring more solid data.